2016
DOI: 10.3892/ol.2016.5336
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor β1 enhances stemness of head and neck squamous cell carcinoma cells through activation of Wnt signaling

Abstract: Abstract. Transforming growth factor β (TGFβ) ligands, including TGFβ1, are multifunctional cytokines known as key regulators of cell growth, differentiation and inflammation. Dysregulated TGFβ signaling is common in numerous solid tumors, including head and neck squamous cell carcinoma (HNSCC). Previously, TGFβ ligands were also reported to be associated with an enhancement of stemness in glioma stem-like cells. However, their role in HNSCC cancer stem cells (CSCs) has not been explored. The present study dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 25 publications
0
18
1
Order By: Relevance
“…What we are discovering is that chemoresistance is much more than the overexpression of drug efflux transporters or the modulation of the cell’s DNA damage response, but rather many signaling pathways related to the stem-like phenotypes of CSCs are also intimately linked to CSC chemoresistance. Such is the case for Hedgehog (Hh), NF-κB, Notch, AKT1, Tumor growth factor-beta (TGF-β) or Wnt/β-catenin signaling pathways, all of which are both signaling pathways upregulated in CSCs and pathways that can promote chemoresistance [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ] ( Figure 3 ). Along these lines, CSCs overexpress or silence numerous pathways and/or factors in order to enhance their inherent resistance to different chemotherapeutics.…”
Section: Pancreatic Csc (Pacsc) Characteristicsmentioning
confidence: 99%
“…What we are discovering is that chemoresistance is much more than the overexpression of drug efflux transporters or the modulation of the cell’s DNA damage response, but rather many signaling pathways related to the stem-like phenotypes of CSCs are also intimately linked to CSC chemoresistance. Such is the case for Hedgehog (Hh), NF-κB, Notch, AKT1, Tumor growth factor-beta (TGF-β) or Wnt/β-catenin signaling pathways, all of which are both signaling pathways upregulated in CSCs and pathways that can promote chemoresistance [ 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ] ( Figure 3 ). Along these lines, CSCs overexpress or silence numerous pathways and/or factors in order to enhance their inherent resistance to different chemotherapeutics.…”
Section: Pancreatic Csc (Pacsc) Characteristicsmentioning
confidence: 99%
“…The tumour‐suppressive role of miR‐198 has been demonstrated in several other cancers such as pancreatic, colorectal, liver and lung cancer . FSTL1 promotes cell survival, invasion and metastasis in glioma, liver, oesophageal SCC and lung cancer . Given the wide range of miR‐198 targets being distinct in different tissues and the modulation of various signalling pathways by FSTL1 in different cancers, miR‐198/FSTL1 molecular switch may be a master controller in physiological wound healing and cancer.…”
Section: Noncoding Rnas In Wound Healing and Cancermentioning
confidence: 99%
“…A series of therapies have been applied in the treatment of HNSCC, including surgery, radiotherapy, neoadjuvant chemotherapy and a combination of these methods (16). However, the 5-year survival rate of this disease has not evidently increased in last 30 years and remains at ≤50% (17)(18)(19)(20)(21). Accumulating evidence suggested that deregulation of TGF-β signaling is of great importance in HNSCC and may be the result of defected TGF-β signaling (22)(23)(24).…”
Section: Transforming Growth Factor-β Signaling In Head and Neck Squamentioning
confidence: 99%